Analisis Faktor-Faktor yang Mempengaruhi Urban Sprawl di Kawasan Cekungan Bandung - Lutfia Nursetya Fuadina; Ernan Rustiadi; Andrea Emma Pravitasari (Diponegoro University, 2021)
Bandung Metropolitan Area is the second largest metropolitan area in Indonesia. Bandung Metropolitan Area also represents the type of metropolitan in Asia which has massive urbanization characteristic that caused by increasing economic growth. This research aims to analyze the spatial diversity of the factors influencing urban sprawl in Bandung Metropolitan Area. The data used in this study were secondary data consisting of Landsat satellite imagery and facilities data obtained from the Central Statistics Agency (BPS) in the year of 2003 and 2014. The methodology used in this study was Geograpically Weighted Regression (GWR) analysis. The results showed that each variables has a different influence on each locations. Population density variable has a positive effect on the percentage of built up area. Whereas the variable of distance to Bandung City, the percentage of paddy field area, the percentage of forest area, and the distance to the toll road has a negative effect on the percentage of built up area. While the effect of the District Development Index variable toward the percentage of built up area varies in each research location.